Multichannel comb filter based on linearly chirped fiber Bragg grating and DC phase shift - Sun, Guodan; Wang, Rong; Pu, Tao; Wang, Hongbo; Wei, Zhihu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
A novel approach to implement high channel-count comb filters based on a DC phase shift is proposed. Various channel spacings can be achieved by a single chirped phase mask and a submicrometer-precision translation stage. Simulation and experiment show that arbitrary phase shifts introduced by DC refractive index modulation can be achieved. An multichannel comb filter with channel spacing of 100 GHz, 50 GHz and 40 GHz is implemented with the same phase mask. A comparison between the proposed DC phase shift and traditional discrete phase shift is made.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 791-797
Keywords: optyka; optical communication band; fiber Bragg grating; comb filter; DC refractive index modulation; phase shift